2008
DOI: 10.1196/annals.1429.013
|View full text |Cite
|
Sign up to set email alerts
|

Eating Disorders and Menstrual Dysfunction in Adolescents

Abstract: Menstrual dysfunction is a common feature of all eating disorders and results in significant medical complications. The etiology of menstrual dysfunction is multifaceted and the result of a complex interplay of many factors including weight loss, decreased body fat, hypoleptinemia, abnormal eating attitudes and behaviors, exercise, and psychological stressors. This chapter will review the prevalence of menstrual dysfunction in adolescents with eating disorders, its multifactorial etiology, the evidence-based p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 123 publications
(253 reference statements)
2
24
0
2
Order By: Relevance
“…Regarding adolescents, several authors have pointed out difficulties in applying the current DSM-IV criteria of EDs on individuals in physical as well as psychological development (Bravender et al, 2007;Chamay-Weber et al, 2005;Couturier & Lock, 2006b;Nicholls, Chater, & Lask, 2000;Vyver, Steinegger, & Katzman, 2008). In accordance with previous findings, the proportion of patients with a bulimic disorder at baseline in this study was significantly higher for adults than for adolescents (Fisher, 2003;Peebles, Wilson, & Lock, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…Regarding adolescents, several authors have pointed out difficulties in applying the current DSM-IV criteria of EDs on individuals in physical as well as psychological development (Bravender et al, 2007;Chamay-Weber et al, 2005;Couturier & Lock, 2006b;Nicholls, Chater, & Lask, 2000;Vyver, Steinegger, & Katzman, 2008). In accordance with previous findings, the proportion of patients with a bulimic disorder at baseline in this study was significantly higher for adults than for adolescents (Fisher, 2003;Peebles, Wilson, & Lock, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…One such mechanism is the loss of menstrual function, which is understood as a common biological response to starvation that serves to conserve energy. 46 Our previous finding that the frequency of menstrual disturbances is predicted by the magnitude of the energy deficit, 20 as well as the high prevalence of menstrual disturbances among anorexia nervosa patients 47 and energy-deficient exercising women, 48 suggest that this adaptation is more likely to occur at the lower end of the adiposity spectrum. As such, prediction equations may need to be refined in normal-weight women to account for metabolic adaptations exclusive to normal-weight or underweight women, which also has important implications for our understanding of metabolic aberrations and weight management in eating disorder patients.…”
Section: Metabolic Adaptationsmentioning
confidence: 99%
“…A high proportion of women in other studies reported suffering oligomenorrhoea or amenorrhoea and these have been associated with body mass index (BMI) and other complications such as polycystic ovary syndrome (PCOS), hirsutism or infertility [8][9][10]. Menstrual disorders have multiple etiologies [11] and studies of associated variables have found relationships with diet and eating disorders [12][13][14], exercise and BMI [11,15,16], stress [17,18] and chronic diseases [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%